Distracting tasks have persisting effects on young and older drivers' braking performance. (October 2021) - Bock, Otmar; Stojan, Robert; Wechsler, Konstantin; Mack, Melanie; Voelcker-Rehage, Claudia
Graphical abstract: Highlights: Distracting activities can have long-term effects on drivers' braking responses. Distractors can increase braking reaction time even after a 12 s delay. Persistent effects of distractors on braking responses show little age-dependence. Abstract: It is well established that car driving performance suffers when the driver concurrently engages in a distracting activity, such as talking on a cell phone. The present study investigates whether the effects of driver distraction are short-lived, or rather persist for some time. Age-related differences are evaluated as well. Sixty-three young and 61 older adults were tested in a driving simulator. They were asked to follow a lead car that drove at a constant speed, and to concurrently engage in a pseudorandom sequence of distracting tasks (typing, reasoning, memorizing). When the lead car braked, participants had to brake as well to prevent a collision. The stimulus onset asynchrony between the braking task and the last preceding distraction was 11.49 ± 1.99 s. Each person was tested once in a multitasking condition (as described above), and once in a control condition without distracting tasks. Outcome measures quantified distance keeping and lane keeping while participants braked to the lead car. We found that braking responses differed significantly between conditions; this difference could be interpreted as a combination of performance deficits and compensatory strategies in the multitasking condition compared to the control condition. We also found significant differences between age groups, which could be interpreted similarly. Differences between age groups were less pronounced in the multitasking than in the control condition. All observed effects were associated with participants' executive functioning. Our findings confirm that distractions have an impact on braking responses, and they document for the first time that this impact can persist for about 11.5 s. We attribute this persistence to a task set effect, and discuss the practical relevance of our findings.